Efktivitas Peran Mediator Dalam Penyelesaian Sengketa Hubungan Industrial Pada Dinas Tenaga Kerja Dan Transmigrasi Kabupaten Lombok Timur - Muh. Syamsul Rizal (Fakultas Hukum Universitas Gunung Rinjani, 2024)
This study aims to find out and analyze the effectiveness of the role of mediators in resolving industrial relations disputes at the Office of Manpower and Transmigration in East Lombok Regency. In this study the researcher formulated the problem of how to resolve industrial relations disputes according to statutory regulations, and how to carry out the role of the industrial relations mediator function at the East Lombok Regency Manpower and Transmigration Office. This research is an empirical normative research which analyzes how law functions in society and understands law in a practical sense. In this study using a statutory approach (statute approach) by collecting literature study data, then using the conceptual. The results of the study show the role of the mediator in resolving disputes by encouraging the disputing parties to resolve the dispute by deliberation to reach a consensus, then making written recommendations if there is no agreement, further notifying the need for the results of the collective agreement to be registered at the Industrial Relations Court. Obstacles in resolving industrial relations disputes at the Office of Manpower and Transmigration of the East Lombok Regency resulted in a vacancy of a Mediator so that the process of resolving disputes was slow, in addition, based on research results and according to the supervisory agency at the office it was explained that there were still workers who did not know the procedures settlement of industrial relations in a bipartite manner, and there is no provision for separate payments made by employers and workers/labourers.